Peran Pemerintah dalam Pemenuhan Hak Atas Pendidikan bagi Anak Berkonflik dengan Hukum - Yuliana Primawardani (Badan Strategi Kebijakan Hukum, 2013)
Children are the future generation of the state, consequently the state has the obligation to provide care and protection of children's rights, including children in conflict with the law. One of the rights that should be protected is the right to education. Nevertheless, there are still children in conflict with law in judicial proceedings who have not obtained their rights to education. These facts were caused by several things, such as the lack of quality and quantity of human resources, the lack of infrastructure, budget, and educators. Hence, there is a need for attention by the government to address these issues, so that children in conflict with the law can continue to obtain their rights during the judicial process.